Observations of volcanic earthquakes and tremor at Deception Island - Antarctica - Alguacil, G.; Almendros, J. C.; Del Pezzo, E.; Garcia, A.; Ibañez, J. M.; La Rocca, M.; Morales, J.; Ortiz, R. (Annals of Geophysics, 1999)
Deception Island - South Shetlands, Antarctica is site of active volcanism. Since 1988 field surveys have been carried out with the aim of seismic monitoring, and in 1994 a seismic array was set up near the site of the Spanish summer base in order to better constrain the source location and spectral properties of the seismic events related to the volcanic activity. The array was maintained during the Antarctic summer of 1995 and the last field survey was carried out in 1996. Data show the existence of three different groups (or families) of seismic events: 1) long period events, with a quasi-monochromatic spectral content (1-3 Hz peak frequency) and a duration of more than 50 s, often occurring in small swarms lasting from several minutes to some day; 2) volcanic tremor, with a spectral shape similar to the long period events but with a duration of several minutes (2-10); 3) hybrid events, with a waveform characterised by the presence of a high frequency initial phase, followed by a low frequency phase with characteristics similar to those of the long period events. The high frequency phase of the hybrid events was analysed using polarisation techniques, showing the presence of P waves. This phase is presumably located at short epicentral distances and shallow source depth. All the analysed seismic events show back-azimuths between 120 and 330 degrees from north (corresponding to zones of volcanic activity) showing no seismic activity in the middle of the caldera. Particle motion, Fourier spectral and spectrogram analysis show that the low frequency part of the three groups of the seismic signals have similar patterns. Moreover careful observations show that the high frequency phase which characterises the hybrid events is present in the long period and in the tremor events, even with lower signal to noise ratios. This evidence suggests that long period events are events in which the high frequency part is simply difficult to observe, due to a very shallow source and/or hypocentral distance higher than that of ...